THE ROLE OF TP53 GENE MUTATION IN THE SURVIVAL OF NON-SMALL CELL LUNG CANCER PATIENTS - Vynnychenko, Oleksandr; Moskalenko, Yuliia; Moskalenko, Roman (Eastern Ukrainian Medical Journal, 2025)
Protein p53 is a surrogate but a highly informative marker for determining a TP53 gene mutation. The primary roles of this protein include the preservation of genome stability and the inhibition of cancer development. Alterations in p53 function and TP53 gene mutations are common in different cancer types, including non-small cell lung cancer (NSCLC). Although a mutation in a major suppressor gene should have catastrophic consequences, the effect on survival is highly ambiguous.The aim of our study was to establish the prognostic role of TP53 gene mutation in radically treated NSCLC patients.Materials and methods. The study included 42 patients who received radical surgical treatment at the Sumy Regional Clinical Oncology Center. All patients had I-IIIB pathological stages of NSCLC and did not receive preoperative radiation therapy or chemotherapy. The follow-up period continued for at least five years. To detect TP53 gene mutation, the immunohistochemistry of NSCLC tissue samples with antibodies against the p53 protein was performed. Pearson χ2 test, log-rank test, and Kaplan-Meier method were used for statistical evaluation. The results were considered statistically significant at p < 0.05. Statistical analysis was performed using Stata V.18.0 software (StataCorp, Texas, USA; https://www.stata.com; 2024).Results. When analyzing the relationship between p53 expression and histological variants of NSCLC, a higher frequency of p53-mut was found in patients with squamous cell lung carcinomas (p=0.012). Other clinicopathological characteristics, including age, sex, tumor stage, category N, and smoking status, did not correlate with p53 expression. The expression of p53-mut was determined in 19 (45.2%) of 42 tumor tissue samples and included 14 (73.7%) samples of squamous cell carcinomas and 5 (26.3%) samples of adenocarcinomas. Univariate analysis showed that NSCLC patients with stages IA-IIA, category N0, p53-mut, never smokers, female gender, and age younger than 60 had better recurrence-free and overall survival. However, no statistically significant difference between the groups was found. Evaluation by histological variant showed that patients with squamous cell carcinoma and TP53 gene mutation had better recurrence-free survival than patients with wild-type TP53 (Log-rank p=0.0490), while adenocarcinoma patients did not demonstrate difference in survival (Log-rank p=0.8003).Conclusions. TP53 gene mutation is present in 45.2% of patients with NSCLC, 25.0% with adenocarcinomas, and 63.6% with squamous cell lung carcinomas. Although patients of the studied cohort with squamous cell carcinomas and mutant p53 had better recurrence-free survival, we cannot conclude that a mutation in the TP53 gene is associated with a favorable prognosis. The obtained results only confirm that the mutation in the TP53 gene does not always have a negative impact on survival. Next-generation sequencing and the application of the evolutionary action of the p53 approach may provide more effective clinical decisions for predicting survival in patients with NSCLC.